Protein-engineered biomaterials: Nanoscale mimics of the Extracellular Matrix - Romano, Nicole (2010)
BACKGROUND: Traditional materials used as in vitro cell culture substrates are rigid and flat surfaces that lack the exquisite nano- and micro-scale features of the in vivo extracellular environment. While these surfaces can be coated with harvested extracellular matrix (ECM) proteins to partially recapitulate the bio-instructive nature of the ECM, these harvested proteins often exhibit large batch-to-batch variability and can be difficult to customize for specific biological studies. In contrast, recombinant protein technology can be utilized to synthesize families of protein-engineered biomaterials that are cyto-compatible, reproducible, and fully customizable. SCOPE OF REVIEW: Here we describe a modular design strategy to synthesize protein-engineered biomaterials that fuse together multiple repeats of nanoscale peptide design motifs into full-length engineered ECM mimetics. MAJOR CONCLUSIONS: Due to the molecular-level precision of recombinant protein synthesis, these biomaterials can be tailored to include a variety of bio-instructional ligands at specified densities, to exhibit mechanical properties that match those of native tissue, and to include proteolytic target sites that enable cell-triggered scaffold remodeling. Furthermore, these biomaterials can be processed into forms that are injectable for minimally-invasive delivery or spatially patterned to enable the release of multiple drugs with distinct release kinetics. GENERAL SIGNIFICANCE: Given the reproducibility and flexibility of these protein-engineered biomaterials, they are ideal substrates for reductionist biological studies of cell-matrix interactions, for in vitro models of physiological processes, and for bio-instructive scaffolds in regenerative medicine therapies.